Design Science: Approach to Build Design Thinking for Student - Winta Adhitia Guspara (Graduate School of Institut Seni Indonesia Yogyakarta, 2020)
ABSTRACTThe existence of products (artifacts) was not a major element in the design paradigm. Product is like tools to help for designing scenarios, realizing the future, and building design knowledge. Planning and making of a product should have an interconnection between the user, product and environment (e.g. space, social, ecological). Accordingly, three main aspects work on the interconnection of product existence. First is the